Detoxification of 1,2-dihydroxy- 4-allylbenzene, a major phenolic compound in Piper betle, through glucuronidation using S9 protein of rat liver (Sprague Dawley) - Martati, Erryana (Universitas Ahmad Dahlan, 2018)
1,2-dihydroxy- 4-allylbenzene (DHAB) is a major compound in Piper betle leaf and also a metabolite of safrole metabolism. Epidemilogic studies showed people who have betel quid chewing habit are related to the incidence of oral submucous fibrosis and/or tumor formation. The aims of this research was to study the detoxification through the glucuronidation of DHAB using S9 protein of male rat liver Â (Sprague Dawley) and a co-factor of uridin 5â²-diphosphoglucuronide acid (UDPGA). The results showed that glucuronidation of DHAB using S9 protein of rat liver resulted two isomers of glucuronide metabolites due to the availibility of two active hydroxyl groups that one of them can bind glucuronide but not two of hydroxyl at the same time.